DOI: 10.14264/uql.2020.482
|View full text |Cite
|
Sign up to set email alerts
|

The global biology, ecology and phylogenetic status of black marlin (Istiompax indica)

Abstract: The black marlin [Istiompax indica (Morrow, 1968)] is one of the largest teleost fish and has a continuous distribution throughout tropical waters of the Indo-Pacific. Throughout its range, I. indica has been documented to undertake wide-ranging, transoceanic and transequatorial movements. In coastal waters and on the high seas I. indica may be targeted by commercial and artisanal fisheries, but the majority of the world's landings are as a by-product species of tuna longline and purse seine fisheries. Due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 176 publications
(353 reference statements)
0
6
0
Order By: Relevance
“…Incomplete biological information for samples comprising NPO2 prohibits comparisons Regional movements of striped marlin generally correspond with the genetically distinct populations described here (Domeier, 2006;Holdsworth et al, 2009;Ortiz et al, 2003;Sippel et al, 2007). The and a third population in the South China Sea (Williams, 2018).…”
Section: Biological Context Of Genetically Distinct Populationsmentioning
confidence: 88%
See 1 more Smart Citation
“…Incomplete biological information for samples comprising NPO2 prohibits comparisons Regional movements of striped marlin generally correspond with the genetically distinct populations described here (Domeier, 2006;Holdsworth et al, 2009;Ortiz et al, 2003;Sippel et al, 2007). The and a third population in the South China Sea (Williams, 2018).…”
Section: Biological Context Of Genetically Distinct Populationsmentioning
confidence: 88%
“…Assessment of over 6,000 SNPs for yellowfin tuna in the Pacific Ocean resolved genetically distinct populations in the western South Pacific, central Pacific, and eastern North Pacific oceans (Grewe et al, ), demonstrating regional population structure similar to that observed in the present study. In contrast, analyses of over 1,500 SNPs in black marlin ( Istiompax indica ) identified a single population spanning eastern and western regions of the Indian Ocean; a second population spanning the western South Pacific, central North Pacific, and eastern central Pacific oceans; and a third population in the South China Sea (Williams, ). Identifying mechanisms underlying differences in ocean‐wide patterns of genetic connectivity among large pelagic fishes requires improved knowledge of species' biological characteristics (e.g., thermal preferences, dispersal capabilities, degree of fidelity to natal spawning grounds) and sensitivity to obvious or cryptic barriers to movement.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 11 summarizes these considerations. [128] and (9) Williams (2018) [136]. The shaded purple areas refer to breeding grounds [125,136].…”
Section: Wahoo (Acanthocybium Solandri)mentioning
confidence: 99%
“…[128] and (9) Williams (2018) [136]. The shaded purple areas refer to breeding grounds [125,136]. The insert in the upper right corner shows the catch distribution of black marlin from 1950 to 2016 (blue: low; red: high catches [28]).…”
Section: Wahoo (Acanthocybium Solandri)mentioning
confidence: 99%
See 1 more Smart Citation